Strategic marketing - Mooradian, Todd A.; Matzler, Kurt; Ring, Lawrence J. (Pearson/Prentice Hall, 2012)
An all-purpose approach to strategic marketing management. Because strategic marketing is the essential marketing activity, Mooradian provides readers with a highly applied decision-making framework and exploration of the tools that can be used to solve marketing problems